The Effect of Furnace Temperature and Precursor Concentration Ratio to The Characteristics of Nanocomposite ZnO-Silica - Iva Maula; Widiyastuti Widiyastuti; Tantular Nurtono; Fadlilatul Taufany; Siti Machmudah; Sugeng Winardi (Institut Teknologi Sepuluh Nopember, 2014)
Zinc Oxide is a semiconductor with relatively non-toxic, cheap and abundant properties which can be applied to LEDs. ZnO colloids are unstable due to further chemical reactions and coagulation so the addition of silica is needed to inhibit the growth of ZnO. ZnO was synthesized using sol-gel method by hydrolyze zinc acetate dihydrate in ethanol solution. Silica colloids was prepared by dissolving waterglass in distilled water at a temperature of 60 °C then passed into cation resin that has been activated using 2N HCl for ion exchange with Na+ to H+. In this study, the spray drying method was used to produce ZnO-silica nanocomposite. Morphological characterization of particles formed was analyzed using Scanning Electrostatic Microscope (SEM) (Zeiss Evo MA LS, Cambridge, England). X-Ray Diffraction (XRD) (Cu-Kα 1.54 A0, 40 kV, 30 mA, X’pert Pro, PAN alytical, Netherlands) and Fourier Transform Infrared (FTIR) (Therniscientific Nicolet iS10, US) were used to analyze the crystallinity and group functionalization, respectively. The results show that more particles are formed on 10% concentration volume of ZnO colloids rather than 5%.